Breaking Bad or Good: A Case Report and Literature Review of Acute Reversible Methamphetamine Associated Cardiomyopathy - Agarwal, Kriti; Chidharla, Anusha; Aedma, Surya Kiran; Al-Awwa, Ahmad; Patel, Urvish K.; Elias, Sameh (Cardiology and Cardiovascular Medicine, 2022)
Introduction: Methamphetamine use has been rising globally and results in significant morbidity and mortality. Methamphetamine is well known to affect multiple organs including neurological, cardiovascular, pulmonary, and renal. Cardiovascular manifestations like arrhythmias, pulmonary artery hypertension, cardiomyopathy, and cardiac arrest can occur from increased inflammation, myocardial fibrosis, and electrical remodeling. Case Presentation: We present a rare case of a 39-year-old man with chronic methamphetamine abuse presenting with worsening shortness of breath and palpitations. Patient was eventually found to have acute onset left ventricular systolic dysfunction (ejection fraction 25-30%) from methamphetamine associated cardiomyopathy. He had a prolonged hospital course, however, a repeat echocardiogram performed 2 weeks later demonstrated near normal left ventricular function (ejection fraction 50-55%). Conclusions: This case emphasizes the temporal effects of drug overdose on the cardiovascular system and its life-threatening complications. It is aimed at raising awareness about consideration of methamphetamine abuse as an important etiological factor when evaluating patients presenting with left ventricular systolic dysfunction and the importance of cessation of drug usage leading to reversal of cardiomyopathy.